Quantification of H3.1-nucleosomes using a chemiluminescent immunoassay: A reliable method for neutrophil extracellular trap detection - Marion Wargnies; Guillaume Rommelaere; Julie Candiracci; Dorian Pamart; Robin Varsebroucq; Florian Jibassia; Finley Serneo; Virginie Laloux; Olivia Thiry; Fanny Lambert; Alison Lobbens; Priscilla Van den Ackerveken; et al. (PLoS ONE, 2025)
Neutrophil extracellular traps (NETs) are chromatin-based web-like structures released by activated neutrophils in response to infectious agents. Overproduction or insufficient clearance of NETs contributes to dysfunction of immune response and disease pathogenesis, underlying the importance of early detection and monitoring of NET levels in clinical samples. While existing methods for NETs detection and quantification face limitations, there is a pressing need for a reliable, sensitive, and clinically applicable assay. Since NETs consist of long strains of decondensed chromatin, with nucleosomes as their basic units, we propose circulating H3.1-nucleosomes as biomarkers for NETs detection in clinical plasma samples. In the initial phase of our study, we confirmed the presence of H3.1-nucleosomes by immunofluorescence and immunoprecipitation experiments in two in vitro NET models: neutrophil-like cells differentiated from the HL-60 cell line, and primary neutrophils isolated from whole blood, both treated with either phorbol 12-myristate 13-acetate or calcium ionophore A23187 to induce NETs formation. Subsequently, we developed and analytically validated a chemiluminescent immunoassay for the quantification of circulating H3.1-nucleosomes in plasma. This fully automated assay demonstrates convincing analytical performance in parameters including sensitivity, precision, linearity and reproducibility. Overall, by measuring the H3.1-nucleosome levels in plasma samples from patients suffering from NETs-related diseases compared to healthy donors, we demonstrated the assay’s clinical value in identifying NETs-associated pathologies and its potential utility for disease management.